Meningkatkan Kualitas Tidur Bayi Berat Badan Lahir Rendah Menggunakan Terapi Qur'an Murottal - Syfa Fauziah; Ayuda Nia Agustina (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Hospitalized babies will experience sleep deprived as a result of adaptation processes, as well as examination procedures that may affect their sleeping phase. This study aimed to describe interventions for increasing sleep quality using the Qur’an murattal therapy. Case Presentation: Two cases of low birth-weight (LBW) babies were studied in the perinatology room. Mrs. D’s baby girl was born at 36 weeks of gestational age, with a chronological age of 1 day and a birthweight of 2,400 grams. Mrs. R’s baby girl was born at 38 weeks of gestational age, with a chronological age of 5 days and a birthweight of 2,000 grams. Both babies were treated in an incubator and received no medical therapy. They were easily awakened and fussy when nurses were interacting with fellow nurses or other health workers. Result: The two babies were given the qur’an murattal therapy recited by sheikh mishari bin rashid alafasy once a day for 30 minutes. The therapy was given through headphones placed in the incubator with sound noise level set to 40 dB. There was an increase in the frequency and duration of quiet sleep in both subjects during murottal therapy. the increase in sleep duration in both babies was 6 hours every day, and the babies were not fussy. Conclussion: This case study concludes that the qur’a murattal therapy with a noise level of up to 40 dB could be increase newborns sleep in the perinatology room.